A Lewis Acid-Promoted Michael Addition and Ring-Expansion Cascade for the Construction of Nitrogen-Containing Medium-Sized Rings - Wang, Jiaming; Li, Jia; Zhao, Changgui (Molecules (Basel, Switzerland), 2023)
A Lewis acid-promoted annulation of azadienes and cyclobutamines was developed. This reaction proceeded through Michael addition and ring-expansion cascade, affording the corresponding nitrogen-containing medium-sized rings with a broad scope in moderate to high yields. The catalytic asymmetric version of this reaction has also been explored using a chiral base.